G274(P) Simulation Training – Transition from Straight to Pigtail Catheter Chest Drain (PCCD) Insertion. (7th April 2014) - Storring, N; Hammerton, C; Lawn, C; Fernandez, R; Rabe, H
Abstract : Aims: Neonatal trainees are infrequently exposed to chest drain insertion due to reduced working hours and low prevalence of pneumothoraces. Procedure performance assessment during simulation using cadaveric models is more effective than traditional clinical education methods. We aimed to evaluate the efficacy of simulation training in teaching PCCD insertion using rabbit carcasses on a tertiary neonatal unit (NICU), in terms of both meeting British Thoracic Society (BTS) competencies and improving participant's procedural confidence and knowledge. Methods: This is a prospective observational study, including advanced neonatal nurse practitioners (ANNPs), nurses and doctors on a NICU. Teaching included a lecture, video and simulation training in small groups using rabbit carcasses. Questionnaires were given to all participants before and after the teaching and simulation sessions. The questionnaires evaluated both knowledge and participants' self-evaluation of confidence at inserting, or in the case of the nurses, assisting in inserting PCCD using a 5-point Likert-scale. After simulation teaching, insertion technique was observed by faculty and compared with a checklist based on BTS. All data were represented as median (range) and analysed using Wilcoxon signed rank; significance was assumed when p < 0.05. Results: 20 datasets were collected, 15/20 were completed sufficiently for full analysis. Postgraduate experience of participants ranged from 3–39 years (median 9.5). 7/20 had previous experience of inserting straight catheters, ranging from 1–50 insertions (median 10) and 3 had previously inserted PCCD (median 3, range 2–10). 10 had no previous experience with any type of neonatal chest drain and 25% had previous teaching. 100% of participants agreed that the teaching was effective and that all session elements were useful to their learning (n = 20). After the simulation training the self-assessment scores of confidence (n = 15) improved from a median score of 1 to 5 (p < 0.001). Knowledge scores (n = 18) improved from a median of 7 to 8 (p < 0.001). 100% of participants assessed (n = 14) were able to meet local standards based on those from the BTS. Conclusion: Using simulation training of pigtail catheter insertion with rabbit carcasses allows ANNPs, doctors and nurses working on a NICU to confidently attempt to insert or assist in the insertion of PCCD.